Antimicrobials from Mushrooms for Assuring Food Safety. Issue 2 (9th February 2017) - Shen, Heng‐Sheng; Shao, Suqin; Chen, Jun‐Chen; Zhou, Ting
Abstract: The interest in discovering and developing natural antimicrobials has significantly increased due to consumer preferences for foods that are free of chemical preservatives while still microbiologically safe. One of the best sources of natural antimicrobials is certain mushrooms (fungi) as many of them not only have nutraceutical functions but also possess antimicrobial properties. This article reviews the available information on mushroom antimicrobials for food safety control. It includes available resources, extraction procedures, antimicrobial activities, and the status of their applications to food safety. The review indicates that there are great potential benefits to be gained from mushroom antimicrobials in food production, processing, and preservation as a biosolution to meet the increasing demands for food quality and safety.